como se resuelve un binomio al cubo , ayuda por favor
Respuestas a la pregunta
Contestado por
2
Guiándote por la formula:
(a+b)³= a³+3(a)²(b)+3(a)(b)²+b³
Ejemplos:
(2x-5)³= (2x)³+3(2x)²(-5)+3(2x)(-5)²+(-5)³=
8x³-75x²+150x+125
SALUDOS
(a+b)³= a³+3(a)²(b)+3(a)(b)²+b³
Ejemplos:
(2x-5)³= (2x)³+3(2x)²(-5)+3(2x)(-5)²+(-5)³=
8x³-75x²+150x+125
SALUDOS
Otras preguntas
Ciencias Sociales,
hace 8 meses
Ciencias Sociales,
hace 8 meses
Matemáticas,
hace 8 meses
Filosofía,
hace 1 año
Matemáticas,
hace 1 año
Castellano,
hace 1 año